Managing information - Garai, Hugh (Gower management workbooks.)
This guide is based on a radical approach to the handling of information, where success goes to those who "work smarter, not harder". From it the reader learns how to survive and thrive under incessant bombardment from data of every conceivable kind. The workbook shows how to achieve more by doing less, and introduce the reader to ways of thinking and acting to help create a new framework for information handling. With the aid of examples, tips and exercises, the reader can become a beneficiary of the IT revolution rather than one of its victims.